Incorporating parental values in complex paediatric and perinatal decisions - Geurtzen, R; Wilkinson, DJC (Elsevier, 2024)
Incorporating parental values in complex medical decisions for young children is important but challenging. In this Review, we explore what it means to incorporate parental values in complex paediatric and perinatal decisions. We provide a narrative overview of the paediatric, ethics, and medical decision-making literature, focusing on value-based and ethically complex decisions for children who are too young to express their own preferences. We explain key concepts and definitions, discuss paediatric-specific features, reflect on challenges in learning and expressing values for both parents and health-care providers, and provide recommendations for clinical practice. Decisional values are informed by global and external values and could relate to the child, the parents, and the whole family. These values should inform preferences and assure value-congruent choices. Additionally, parents might hold various meta values on the process of decision making itself. Complex decisions for young children are emotionally taxing, ethically difficult, and often surrounded by uncertainty. These contextual factors make it more likely that values and preferences are initially absent or unstable and need to be constructed or stabilised. Health-care professionals and parents should work together to construct and clarify values and incorporate them into personalised decisions for the child. An open communication style, with unbiased and tailored information in a supportive environment, is helpful. Dedicated training in communication and shared decision making could help to improve the incorporation of parental values in complex decisions for young children.